Les relations canado-américaines : Nationalisme et continentalisme - Balthazar, Louis (Études internationales, 1983)
This paper's objective is to bring forth some elements which confirm the following hypothesis : Canada is consigned to continentalism, namely to economic and cultural integration with the United States though this fact is shrouded in a Canadian nationalism of sorts. The continentalist mentality is rooted in the history of British North America, inhabited mostly by refugees from America who have remained inherently "Yankees" in spite of their anti-americanism. The Confederation itself is based on a sort of complicity with the United States. More recently there were talks of a "North American nationality", and continentalism both cultural and economic has come to be seen as a 'force of nature" which the governments, at the most, put into a chanelling process. Still, it is possible for Canadian nationalism to exist provided it does not go beyond the threshold whence it would run headlong into the continental mentality. Canada has defined itself through an international or non-national perspective far too long for today's nationalism not to remain weak and poorly established. But the Americans whose "manifest destiny" has succeeded in spreading over Canada without even their having tried to hoist their flag there find it to their advantage to maintain some form of Canadian sovereignty. Canada as a "friendly nation" can be of use to Washington. That is why there are almost as many advocates for Canada's independence in the United States as there are north of the border. Canadian nationalism can thus further the interests of some Canadian elites without seriously prejudicing continental integration which can very well afford not to be set up into formalized structures.